Comparing two different daily disposable lenses for improving discomfort related to contact lens wear. Issue 3 (June 2016) - Michaud, Langis; Forcier, Pierre
Highlights: Patients reporting moderate to severe symptoms of contact lens discomfort (CLD) can be helped by the use of nelfilcon A or delefilcon A daily disposable lenses. For those showing marginal CLD, refiting them in delefilcon A can improve their symptoms but nelfilcon A failed to make a significant reduction in their symptoms. Consequently, practitioners should base their clinical decision on symptoms as identified with validated questionnaires. CLD improvement is material dependant. Delefilcon A represents a better alternative to switch patients into daily disposable modality. Abstract: Purpose: This study aimed to compare two daily disposable lenses to reduce lens-induced discomfort (CLD) among different populations of symptomatic wearers. Methods: This was a multicenter, crossover, study. Subjects were contact lens wearers reporting CLD. Subjects (76) were randomly assigned to wear Nelfilcon A (NF) then Delefilcon A (DF)- group A- or vice-versa (group B). Tear break-up time (TBUT), corneal (CS) and conjunctival staining (CJS) were graded at every visit. Subjects'symptoms were evaluated with Contact Lens Dry Eye Questionnaire (CLDEQ-8) and a research questionnaire (Université de Montréal). Results: Compared to baseline (BL), TBUT did not vary (BL) 6.7 + 2.1 s vs. 6.7 + 1.8 s (NF) vs. 6.4 + 1.9 (DF) ( F  = 1.69; p  = 0.201) NF wearers were more at risk of developing moderate CJS (odds ratio 14.324; 95% CI 3.103–66.126) and more likely to show increased CS (odds ratio 8.754; 95% CI 2.181–35.146). Comfortable hours of wear reported at BL (7.6 + 2.3 h) did not improve significantly with NF lenses (8.5 +  2.6 h; F  = 1.095; p  = 0.394) but increased by 22% with DF lenses (10.7 + 3.0 h; F  = 2.434; p  = 0.031). The total CLDEQ-8 score was improved with DF lenses (BL 17.2 vs. NF 16.1, p  = 0.397; vs. DF 8.3, p  < 0.001), especially on more symptomatic subjects. In the end, 92% of patients preferred to switch over DD lenses, 78% selecting DF material for the future. Conclusion: Outcome from switching CLD wearers to DD lenses is material related. It seems that initial severity of the symptoms could be also a factor to consider.